(untitled) (Research, Society and Development, 2021)
The development of products and processes which are more ecological has been a source of interest in research in recent decades. Thus, researchers have developed several methods to improve the synthesis of oxides and metals in a more ecological way. Green synthesis has become a method that is being widely used for presenting low temperature, low cost and great availability of raw material. Some biological sources such as fungi, bacteria and plants are used in this route, but plant extracts are the most used in the literature. Various parts of the plant such as the roots, bark, flowers, fruits, stem, seeds, and leaves are rich in secondary metabolites such as: flavonoids, phenols, steroids, terpenoids, alkaloids, saponins and phenolic compounds, which play an essential role in the complexation, polymerization, capping and stabilization processes that generate oxides. The methodology used in the synthesis process significantly interferes in some properties and characteristics of the same oxide as its morphology. In this sense, this paper presents a review on green synthesis in obtaining oxides and their morphologies.